Fabrication of chitosan membrane : the effect of evaporation times on membrane performance in oily waste water treatment - Pachiapan, Murugesan (2008)
Fabrication of chitosan membrane and the effect of evaporation times on membrane performance in oily wastewater treatment are studied in this paper. Chitosan homogenous membranes were fabricated by casting a chitosan/acetic acid solution, and then evaporate it for different periods of time, followed by chemically cross-linking with sulfuric acid. The separation tests using the resulting membranes demonstrate that the chitosan membranes are capable of separating water–oil mixtures in wastewater. The optimized conditions for chemical cross-linking of membranes were found to be 0.5M of the cross-linking reagent (sulfuric acid) and 10 min reaction time at ambient temperature. The preparation time of chitosan membranes is the key factor to evaluate performance of separating water–oil. It was observed in orthogonal tests that the effect of membrane preparation time on the separation factor was significant. The highest separation factor was 1170 and it occurred at 120 minutes of evaporation time. The highest separation index also occurred at this period of time. The highest separation index was 1092609. These results suggested, 120 minutes is the most perfect evaporation time to produce an efficient chitosan membrane which can extract oil from waste water. As a conclusion, the present work clearly correlates the separation performance of wateroil by using the chitosan membrane resulting from the different of evaporation time.